A DATA EXCHANGE NEUTRAL FORMAT FOR FINITE ELEMENT CODES USING AN INTELLIGENT ELEMENT CLASSIFICATION (Revista CIATEC-UPF, 2012)
This work presents the basis of the Finite Element Markup Language (FEML) proposal and also an intelligent tool for the recognition and classification of finite elements families used in conjunction with the above XML schema. The need for the classification becomes clear due to the necessity of a mapping between the several elements in a given code and the FEML format. A tree-type search could be used but it can lead to a lengthy if-then-else sequence to perform the matching. The use of a database-type classification could also be an option; however the search mechanism would still be required. Moreover, the use of an intelligent-type classification is also able to accommodate changes in the element families to be classified and new elements can be added with minimum effort. Here, the so-called intelligent classification uses the technology of artificial neural networks, specifically through of application the Self-organizing Map Networks and the Learning Vector Quantization. To carry out this task, the network receives the attributes of the elements and makes its classification, in terms of equivalent (or similar, less specialised) elements. At the end, it allows for the interface programs to “translate” between a specific (proprietor) format and the neutral format, in an intelligent way, minimizing errors due to manual data transcription and eliminating the necessity of searching the entire tree of elements. Keywords: Classification; finite elements; artificial neural network; self-organizing map; learning vector quantization; XML schema.